ELECTIONS ET RIVALITES ETHNIQUES EN RDC : Regard rétrospective sur le phénomène « ABAMBUTU… » dans la circonscription électorale de Punia. - CT. Victor NONGA WALEMBA, (IJRDO - Journal of Social Science and Humanities Research, 2019)
This article focuses on electoral practices and ethnic rivalry in the DRC, an experience in the Punia constituency.According to our sources and to our investigations, the electoral choice in 2006 in the electoral district of Punia was the result of a "political marketing" based on ethno or tribal-political values. projects of the companies, the competence, the sense of responsibility, honesty or frankness, the capacity of persuasion, the required profile of the candidate ... were all rejected criteria in favor of a true tribal infeodation.One understands then how much an adage Komo (ABAMBUTU ...), tinged with tribalism and colored politically served as a strategy "maker of the ROI" whatever the fallout that followed.For a radiant and non-confrontational electoral process in the DRC and PUNIA in particular; values ​​such as inclusivity, competence, peace, peaceful alternation, social cohesion ... before, during and after the elections must be more and more privileged. Here are some good reasons to consider s solutions poured into the following lines.